Identificação e avaliação da qualidade das águas pluviais lançadas no rio Lonqueador no perímetro urbano de Francisco Beltrão - PR - Basso, Raul Fernando Schwinn (2023)
The municipality of Francisco Beltrão/PR located in the southwest of Paraná, has been growing in recent years. As a result, basic sanitation suffers from high demand. Thus, the number of possible clandestine effluents released along the rivers that cross the city becomes common, mainly in the Lonqueador River. This river runs through the city from the south, in the Água Branca neighborhood, passing through the city center until it merges with the Marrecas River, which follows its natural course. With the support of georeferencing, this work aims to identify and record points of stormwater structures with clandestine sewage connections on the banks of the Lonqueador River. With the analyzes of COD, BOD, pH and other important parameters, it was possible to identify whether these rainwater releases have in their contamination effluents that are not treated or contaminated with polluting materials, or just rainwater from the drainage of impermeable areas in the context of the hydrographic basin of the Lonqueador River.